Caracterização da evapotranspiração no Pantanal Mato-Grossense fundamentada pela teoria dos sistemas complexos - Taques, Luciene de Mello (2018)
The objective of this work is to characterize evapotranspiration in a periodic flood area in the Mato Grosso Pantanal, based on Complex Systems Theory. The Pantanal evapotranspiration data were collected between March 2012 and April 2013 by sensors installed in a 28 m high tower, located in the Baia das Pedras region, in the municipality of Poconé, Mato Grosso, Brazil. The method used is to reconstruct the characteristic attractors of the evapotranspiration variable of the Pantanal Mato Grosso from drought, flood, flood and ebb periods, determining its dimensionality: correlation dimension of the time series (d) and dimension of immersion in the phase space (n ), comparing them with results obtained in two distinct ecosystems: Amazon-Cerrado transition forest (Sinop) and Amazonia (Reserva Jaru) in the years 2007 and 2008 respectively. The results show that the Mato Grosso Pantanal from the point of view of evapotranspiration is a wellbehaved ecosystem. The period under analysis did not show a stochastic tendency but a behavior that tended to determinism, with the four seasonal periods showing little difference in relation to dimensionality. There is a difference in the dynamics of evapotranspiration between the Pantanal Mato Grosso, the Amazon-Cerrado transition forest (Sinop) and the Amazon (Jaru Reserve) in relation to the dimensionality of the attractors reconstructed for dry and humid periods.